Neuroprotective Effect of Simvastatin via Inducing the Autophagy on Spinal Cord Injury in the Rat Model. (11th October 2015) - Gao, Kai; Wang, Guannan; Wang, Yansong; Han, Donghe; Bi, Jing; Yuan, Yajiang; Yao, Tianchen; Wan, Zhanghui; Li, Haihong; Mei, Xifan
Abstract : Simvastatin, an inhibitor of 3-hydroxy-3-methylglutaryl-coenzyme A reductase, is invariably used to treat cardiovascular diseases. Simvastatin has been recently demonstrated to have a neuroprotective effect in nervous system diseases. The present study aimed to further verify the neuroprotection and molecular mechanism of simvastatin on rats after spinal cord injury (SCI). The expression of Beclin-1 and LC3-B was evidently enhanced at postoperation days 3 and 5, respectively. However, the reduction of the mTOR protein and ribosomal protein S6 kinase p70 subtype (p70S6K) phosphorylation level occurred at the same time after SCI. Simvastatin significantly increased the expression of brain-derived neurotrophic factor (BDNF) and glial cell line-derived neurotrophic factor (GDNF). Meanwhile, immunofluorescence results indicated that the expression of chondroitin sulfate proteoglycan (CSPG) and caspase-3 protein was obviously reduced by simvastatin. Furthermore, Nissl staining and Basso, Beattie, and Bresnahan (BBB) scores showed that the quantity and function of motor neurons were visibly preserved by simvastatin after SCI. The findings of this study showed that simvastatin induced autophagy by inhibiting the mTOR signaling pathway and contributed to neuroprotection after SCI.